Estimating The Spatially Varying Relationship Between Intimate Partner Violence & Socio-Demographic Variables In Nigeria - Aliu, T. O.; ALADENIYI, O. B.; Aliu, A. H. (Journal of Science, Technology and Innovation Research, 2026)
Violence against women particularly committed by an intimate partner had become a social and public problem across the world. Intimate Partner Violence (IPV) is one of the most common forms of violence against women which includes physical, sexual, and emotional abuse and controlling behaviours by an intimate partner. However, there is limited evidence on the estimating spatially varying relationships that might exist between this violence and socio-demographic variables to determine the pattern of IPV. Therefore, this study examined the spatially varying relationship that exist between IPV and selected socio-demographic variables in Nigeria. This study utilized data obtained from Demographic and Health Surveys (DHS) conducted during the years 2008, 2013 and 2018 survey in Nigeria. Semi-Parametric Geoadditive Regression Model was adopted. Results showed that the spatial distribution pattern of IPV in Nigeria were clustered. The likelihood of experiencing IPV among women in Nigeria was high among those who their partners drank alcohol and women whose wealth index were poorer compared to women whose wealth index were high or very rich. The study concluded that there was a spatial variation in the distribution pattern of intimate partner violence in Nigeria. Also as a woman advanced in age, her exposure to any form of IPV decreased. Therefore, women within the poorest wealth index, who were not gainfully employed and those with low or without education should be considered in the development and implementation of interventions against intimate partner violence in Nigeria. Keywords: Violence, Physical abuse, Sexual abuse, Emotional abuse, spatial pattern